Exploring the relative age effect and nation dominance in olympic boxing, a review of the last decade - Edginton, R.; Gibson, R.; Connelly, C. (Procedia Engineering, 2014)
The aim of the paper was to establish whether a relative age effect (RAE) and nation dominance has been evident in elite-level amateur boxing during major competition (World Championships and Olympic Games) over the last decade. Although recent studies suggest the reverse; RAE research suggests that the older an athlete is, according to their age category when they begin training for sport, the more likely they are to achieve success in that sport. The present study explored the characteristics of male medal winning boxers (N=388) during the last decade, to identify whether trends exist. Medal winners from the aforementioned tournaments (2000 to 2012) were recorded and categorised by weight classification, date of birth, competition date and nation. Age of competitors at the respective competitions were calculated and grouped by result in order to establish age profiles of medallists. The average age in years of medal winners in the last decade was 24 (SD 3.3). The study reports a significant difference between an expected equal distribution and observed distribution of birth dates by year half, quartile and month in amateur boxing. Higher values are recorded for the first quartile and half of the year demonstrating the presence of a relative age effect in medal winning men's amateur boxing in the last decade. Dominance of nations was also explored to identify emerging and successful nations. From the records, Cuba dominated the medal count winning 13.6% of the medals available, closely followed by Russia with 12.6%. The main emergent nation identified was Brazil, going from winning zero medals in both 2001-2004 and 2005-2008 to winning four medals during the 2009-2012 Olympic cycle. The practical implications of average age and RAE findings are to ensure that athlete programmes enhance opportunities for early development based on skills and potential rather than overall ability enhanced by physicality.